An investigation on the diet composition, seasonal variation in feeding intensity and ontogenetic dietary shifts of L. intermedius in Lake Koka - Godana Bekere; Kumsa Leqa; Wako Ogata; Zenawi Asfaw Isaias (African Journal of Environmental Economics and Management, 2014)
The food and feeding habits of the African big barb LABEOBARBUS INTERMEDIUS (Rüpell, 1836) was studied based on 390 gut samples collected in April- May 2011 (dry months) and July- August 2011 (wet months) in Lake Koka, Ethiopia. Frequency of occurrence and volumetric methods of analysis were used in this study. Macrophytes, detritus and insects were the most important food items occurring in 79.1%, 80.0% and 62.5% of the guts, and accounting for 46.3%, 27.5% and 18.2% of the total volume of food, respectively. The contributions of phytoplankton, zooplankton, fish scales and ostracods were relatively low. Macrophytes and detritus were important food items during the wet months occurring in 96.2% and 60.9% of the guts, respectively and comprising 66.1% and 24.0% of the total volume of food items, respectively. The contribution of insects was low during the wet months. Detritus, macrophytes and insects were found to be the dominant food items in all size classes, whereas the contributions of ostracods, fish scales, zooplankton and phytoplankton were low. Based on the results it can be concluded that L. INTERMEDIUS was omnivorous in its feeding habits in Lake Koka.